Construction of new mathematical model in islamic home financing - Puspa Liza, Ghazali; Sharifah Arni, Syed Jaaffar; Nik Hazimi, Mohammed Foziah; Wan Mohd Nazri, Wan Daud; Farah Amalina, Md Nawi; Mustafa, Mamat; Saiful Bahri, Mohammad; Sadad, Mahmud; Abdul Malek, A Tambi (2018)
Islamic financial institution (IFI) provides a few formula of home financing in the market. Normally for income earners in a middle class and bellow‟s category found out that the loan is quiet burden for them plus mortgage takaful only provide coverage for death and total permanent disability (TPD) without loss an effort to work included in the plan. The aim of the study is to derive a new formula of Islamic home financing which included financing and mortgage takaful model for loss an effort to work. By using the concept of profit which is the financing amount is half of the principle loan and consequence to that, a new formula of Islamic home financing can be derive. The new model of mortgage takaful will include loss an effort to work‟s coverage. Hence, this study is focusing on developed a new formula of Islamic home financing and mortgage takaful model by using an integrated model.